334PIncidence and characteristic of adrenal insufficiency due to immune checkpoint inhibitors therapy. (24th November 2019) - Etoh, D; Harada, T; Shimauchi, A; Ibusuki, R; Kayukawa, T; Okamatsu, Y; Inoue, K; Tsubouchi, K
Abstract: Background: Immune checkpoint inhibitors (ICI) have been approved for non-small lung cancer (NSCLC). Adrenal insufficiency (AI) is a distinctive adverse event related to ICI. This can be either primary adrenal gland destruction or interference with corticotrophin (ACTH) secretion by the pituitary gland (secondary). As AI is relatively rare and symptoms and signs of AI are non-specific, the diagnosis of AI is often difficult. To clear the incidence and characteristics of AI related with ICI. We conducted a retrospective single center study. Methods: We reviewed the medical records of patients with NSCLC who received pembrolizumab, nivolumab, atezolizumab or duravalmab at JCHO Kyushu Hospital between Feb 2017 and Jun 2019. Results: A total of 114 patients with NSCLC received ICI. Eight patients (7.0%) were diagnosed with AI. Median age was 67 (range: 54 to 79). Six were male. Six out of eight patients were secondary AI, one patient was primary AI, and one patient was unknown. The median onset of AI from the first dose of ICI was 203 days (range: 38 to 763). The patients presented with fatigue, fever, nausea, diarrhea and/or dizziness. One patient was diagnosed because of repeating COPD/asthma attack. Hypocholesterolemia, hyponatremia, eosinophilia, hypoglycemia, and hyperkalemia were found 4, 2, 3, 1 and 1 out of 8 patients respectively. One patient didn't exhibit any above symptom. All of the patients had rapid resolution of symptoms after hydrocortisone replacement. Conclusions: ICI-associated AI developed in 7.0% of patients requiring hydrocortisone replacement therapy. Symptoms and laboratory abnormalities at the time of onset varied. It is thought that patients using ICI therapy will further increase in the future, and patients who develop ICI-related AI will also increase. Clinicians should deepen their understanding of the nature of AI and provide appropriate information to patients so that AI can be quickly diagnosed and treated. Legal entity responsible for the study: The authors. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.